The interferon or interferon-like substance production of EB3 cells after inoculation with human sera containing Australia antigen - Candeias, J. A. N. (Revista de Saúde Pública, 1975)
The production of interferon or an interferon-like substance by EB3 cell cultures exposed to human sera containing Australia antigen is described. The normal pattern of interferon production by EB3 cells not inoculated with human sera is modified, after exposure to human positive sera for Australia antigen and it is suggested that this modification may provide a criterion for interaction of Australia antigen and EB3 cells.